pH-responsive “supra-amphiphilic” nanoparticles based on homoarginine polypeptides - Praveen, Korra; Das, Soumen; Dhaware, Vinita; Pandey, Bhawana; Mondal, Basudeb; Sengupta, Sayam (ACS Applied Bio Materials, 2019)
pH-responsive “supra-amphiphiles” based on double hydrophilic, positively charged block copolypeptides such as PEG-b-poly-l-lysine together with low molecular weight stimuli-sensitive partners that contain phosphate and carboxylate groups have been widely studied. In contrast, the other widely used cationic polypeptide poly-l-arginine whose cell-penetrating properties are well-known has been much less explored for the synthesis of supra-amphiphile-based nanomaterials. It is also known that the guanidine side chain of arginine binds to carboxylate anions with binding constants that are 2.5 times higher than the corresponding amines of poly-l-lysine. Here, we demonstrate the fabrication of pH-sensitive supra-amphiphilic nanoparticles by simple mixing of PEG2k-b-poly(homoarginine) block copolymer and carboxylic acid containing functional low molecular weight organic compounds. A high yielding three-step methodology was developed for the synthesis of ε-N,N′-di-Boc-l-homoarginine-α-N-carboxyanhydride which was polymerized using amine-terminated PEG (2000 MW) to yield 100% guanine-functionalized polypeptide (PEG2k-b-PHR30) with controlled molecular weights and low PDIs. Incubation of PEG2k-b-PHR30 with four different carboxylic acids (including dexamethasone a glucocorticoid receptor used in cancer therapy) in water leads to the formation of “supra-amphiphilic” nanoparticles (<200 nm size) due to the charge neutralization resulting from the strong interaction between the guanidine group and the carboxylate group. All these nanoparticles were able to encapsulate the hydrophobic dye Nile red with varying efficiency. Although these assemblies were stable at neutral pH, upon lowering the pH of the solution between 4 and 5, the protonation of the carboxylic acids leads to disassembly of these nanoparticles. The cytotoxicity of all four “supra-amphiphilic” nanoparticles varied depending on the carboxylic acid used for their fabrication. While the nanoparticle formed using dioctylbenzoic acid displayed 80% cell viability at concentration of 60 μg/mL, those formed with the steroid deoxycholic acid or dexamethasone showed only 40% cell viability at similar concentrations. Colocalization studies performed using epifluorescence microscopy demonstrate the successful uptake of intact dye-encapsulated nanoparticle inside the cell.